2016
DOI: 10.2308/jeta-51593
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the Readability of SOX 404 Reports

Abstract: This study examines SOX 404 reports with fiscal year-ends between 2004 and 2014 to determine their readability as measured by the FOG Index. We investigate the association between readability and company characteristics, auditor type, opinion type, time period, report content, and report length. We find that the sign and significance of certain associations depend on whether the reports contain material weaknesses. Overall, results show that management's reports are more readable than auditor's reports; longer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 44 publications
6
21
2
Order By: Relevance
“…Meanwhile, we also sought to control for firm size, by inserting the variables firm size (Size it ), operationalized using the natural logarithm of total assets, and firm age (Age it ), operationalized using the logarithm of the years the firm has been registered with the CVM, which is consistent with previous studies (Pinto et al, 2020;Velte, 2018Velte, , 2019. Less readability of the reports is expected as a result of firm size, this being due to the complexity of operations, which increases as the company "matures" and grows (Pinto et al, 2020;Boritz et al, 2016). However, while bigger companies are expected to have less readable reports, younger ones tend to strive to disclose more understandable reports.…”
Section: Control Variablessupporting
confidence: 65%
See 4 more Smart Citations
“…Meanwhile, we also sought to control for firm size, by inserting the variables firm size (Size it ), operationalized using the natural logarithm of total assets, and firm age (Age it ), operationalized using the logarithm of the years the firm has been registered with the CVM, which is consistent with previous studies (Pinto et al, 2020;Velte, 2018Velte, , 2019. Less readability of the reports is expected as a result of firm size, this being due to the complexity of operations, which increases as the company "matures" and grows (Pinto et al, 2020;Boritz et al, 2016). However, while bigger companies are expected to have less readable reports, younger ones tend to strive to disclose more understandable reports.…”
Section: Control Variablessupporting
confidence: 65%
“…According to Asay et al (2017), the increase in data may, in specific situations, hinder the readability of the text and cause an adverse effect on the parties involved, encouraging them to use other sources of information they are familiar with. Boritz et al (2016) verified that, unlike what has been observed in studies such as that of Dyer et al (2017), an increase in the size of the report does not necessarily reduce its readability, as users tend to be accustomed to the language used in such reports. In turn, Lo et al (2017) observed that the readability level of the reports is associated with the manipulation of accounting information, as companies with modified results tend to present more complex reports to conceal earnings management.…”
Section: Introductionmentioning
confidence: 51%
See 3 more Smart Citations